2014
DOI: 10.5430/wje.v5n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Imagined Contact Improves Intentions towards a Hypothetical Peer with Asperger Syndrome but not Attitudes towards Peers with Asperger Syndrome in General

Abstract: The aim of this study is twofold. First, to investigate whether the imagined contact method (an indirect method of contact) can improve behavioural intentions towards a hypothetical peer with Asperger syndrome (AS). Second, to test whether the effect of the method can be generalised on attitudes towards young people with AS in general.Participants were 416 young adolescents (M age= 15.2) who view a power-point presentation introducing a hypothetical male target with AS. A voice-over provided either descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The authors found that this was associated with more positive attitudes, as compared to the results in the control condition describing their disability only (neutral information of the hypothetical classmate). However, other studies have not found an effect of information on attitudes and behavioral intentions toward peers with disabilities (e.g., Fleva, 2015;Swaim & Morgan, 2001). Therefore, results on the role of information are mixed.…”
Section: The Role Of Information About Disabilitymentioning
confidence: 92%
“…The authors found that this was associated with more positive attitudes, as compared to the results in the control condition describing their disability only (neutral information of the hypothetical classmate). However, other studies have not found an effect of information on attitudes and behavioral intentions toward peers with disabilities (e.g., Fleva, 2015;Swaim & Morgan, 2001). Therefore, results on the role of information are mixed.…”
Section: The Role Of Information About Disabilitymentioning
confidence: 92%
“…Five studies assessed three outcomes (Campbell 2007;Gus 2000;Mavropoulou and Sideridis 2014;Ranson and Byrne 2014;Staniland and Byrne 2013), and nine reported data for a single outcome: attitudes (Cook 2017;Frederickson, Warren, and Turner 2005;Gardner et al 2014;James 2011;O'Connor 2016;Reiter and Vitani 2007); actual behaviour (Houston 1998;Owen-DeSchryver et al 2008); and knowledge (Scheil, Bowers-Campbell, and Campbell 2017). Of the remaining 13 studies, six assessed both attitudes and intended behaviour (Campbell et al 2004(Campbell et al , 2005Fleva 2014Fleva , 2015Morton and Campbell 2008;Silton and Fogel 2012;Swaim 1998;Swaim and Morgan 2001), six assessed both attitudes and actual behaviour (Collet-Klingenburg, Neitzel, and LaBerge 2012;Ezzamel 2016;Ezzamel and Bond 2017;Hughes et al 2013;Simpson and Bui 2016;Sreckovic 2015;Sreckovic, Hume, and Able 2017;Whitaker et al 1998), and one assessed knowledge and attitudes (Campbell et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The gender was unreported for two (Mavropoulou and Sideridis 2014;Silton and Fogel 2012). Most were male (n = 8; Campbell 2007;Campbell et al 2019;Campbell et al 2004Campbell et al , 2005Fleva 2014Fleva , 2015Morton and Campbell 2008;Silton and Fogel 2012;Swaim 1998;Swaim and Morgan 2001), and there was one female (Silton and Fogel 2012). From the data reported, the mean age of unfamiliar target children was 12.71.…”
Section: Participantsmentioning
confidence: 98%
See 2 more Smart Citations